Adjunctive yoga v. health education for persistent major depression: a randomized controlled trial. Issue 12 (6th April 2017) - Uebelacker, L. A.; Tremont, G.; Gillette, L. T.; Epstein-Lubow, G.; Strong, D. R.; Abrantes, A. M.; Tyrka, A. R.; Tran, T.; Gaudiano, B. A.; Miller, I. W.
Abstract : Background: The objective of this study was to determine whether hatha yoga is an efficacious adjunctive intervention for individuals with continued depressive symptoms despite antidepressant treatment. Method: We conducted a randomized controlled trial of weekly yoga classes ( n = 63) v. health education classes (Healthy Living Workshop; HLW; n = 59) in individuals with elevated depression symptoms and antidepressant medication use. HLW served as an attention-control group. The intervention period was 10 weeks, with follow-up assessments 3 and 6 months afterwards. The primary outcome was depression symptom severity assessed by blind rater at 10 weeks. Secondary outcomes included depression symptoms over the entire intervention and follow-up periods, social and role functioning, general health perceptions, pain, and physical functioning. Results: At 10 weeks, we did not find a statistically significant difference between groups in depression symptoms ( b = −0.82, s.e. = 0.88, p = 0.36). However, over the entire intervention and follow-up period, when controlling for baseline, yoga participants showed lower levels of depression than HLW participants ( b = −1.38, s.e. = 0.57, p = 0.02). At 6-month follow-up, 51% of yoga participants demonstrated a response (⩾50% reduction in depression symptoms) compared with 31% of HLW participants (odds ratio = 2.31; p = 0.04). Yoga participants showed significantly better social and role functioning and general health perceptions over time. Conclusions: Although we did not see a difference in depression symptoms at the end of the intervention period, yoga participants showed fewer depression symptoms over the entire follow-up period. Benefits of yoga may accumulate over time.